Strategic Management in E-governance : Potential Developments of G2G, G2B, and G2C Services in Azerbaijan - Satiji, Ayhan (ADA University, 2021)
Purpose: Strategic management in e-governance is examined with the application of various concepts. Infrastructure, e-government security, organizational change and issues, training, content and application, management, e-service, and monitoring and evaluation concepts are tested against e-governance. Design/methodology/approach: Experimental analysis is utilized where framing experiment model facilitates how to design survey-based experiment. The sample for the research is collected from the primary data. Three different surveys (G2G, G2B, and G2C) are designed to collect the data. The participants are specifically chosen among the experts whose e-governance knowledge is substantially higher. Ordered Probit Models are used to test the main influencing factors of e-governance in STATA 13. Findings: Utilization of 37 observations from the expert pool shows a considerable variation among the main independent variables, except the e-government security measure. Infrastructure and changing the approach of management concepts predict the factors influencing G2G and G2B e-governance. While infrastructure is negatively associated with G2G e-governance, it has a positive relation with G2B e-governance. Moreover, changing the approach of management is positively associated with G2G e-governance and negatively associated with G2B e-governance. Finally, e-government security is negatively associated with G2B e-governance. Practical implications: Our evidence has policy implications for Azerbaijan aiming to create an e-governance environment. Particularly, Infrastructure and management play a complementary role in increasing e-governance practices on G2G and G2B.
Keywords: Public and International Affairs; E-governance -- Azerbaijan; Strategic management -- Azerbaijan; E-service -- Azerbaijan; Monitoring and Evaluation -- Azerbaijan.